2011
DOI: 10.1007/s00404-011-2177-2
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected ovarian malignancy after conservative laparoscopic surgery: five case series in a half decade of experience

Abstract: The main concern for laparoscopic management of ovarian masses is unexpected malignancy. However, with careful patient selection, proper technique and an experienced operator, laparoscopic treatment of ovarian masses is the best approach and should be implemented, with low risk of unexpected malignancy and recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Whereas a study from Japan, the overall incidence rate of unexpected ovarian malignancy was 1.5%, of which 0.45% was contributed by the postmenopausal group [13]. In a previous study, the author reported the rate of unexpected ovarian malignancy in 0.43% of laparoscopic surgery cases in premenopausal women with benign ovarian mass [14].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Whereas a study from Japan, the overall incidence rate of unexpected ovarian malignancy was 1.5%, of which 0.45% was contributed by the postmenopausal group [13]. In a previous study, the author reported the rate of unexpected ovarian malignancy in 0.43% of laparoscopic surgery cases in premenopausal women with benign ovarian mass [14].…”
Section: Discussionmentioning
confidence: 92%
“…Whereas a study from Japan, the overall incidence rate of unexpected ovarian malignancy was 1.5%, of which 0.45% was contributed by the postmenopausal group [ 13 ]. In a previous study, the author reported the rate of unexpected ovarian malignancy in 0.43% of laparoscopic surgery cases in premenopausal women with benign ovarian mass [ 14 ]. The incidence of unexpected malignancy may vary from 11-19% with surgeon's strategies when laparoscopic surgeries were done for adnexal mass that appeared complex on ultrasonography [ 8 , 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Every year, a large number of women undergo laparoscopic surgery for the removal of ovarian cysts which are initially thought to be benign. However, a small percentage (<2%) of unexpected malignancy has been encountered during postsurgery tumor analysis 18–20. The choice of management becomes straightforward for the surgeon in the case of postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 13% of ovarian cancer patients are younger than 45 years of age. [2][3][4][5] The detection of normal ovarian parenchyma can be challenging. A surgeon can evaluate an ovary visually, by palpation, or by intraoperative ultrasound.…”
Section: Introductionmentioning
confidence: 99%